Menkes kinky hair disease: characteristic MR angiographic findings. - Jacobs, D S; Smith, A S; Finelli, D A; Lanzieri, C F; Wiznitzer, M (American Journal of Neuroradiology, 1993)
We report two cases of Menkes kinky hair disease in which MR and MR angiography were performed. The clinical and imaging features are reviewed. MR demonstrated characteristic cerebrovascular tortuousity and thus may be a valuable aid in diagnosis and follow-up.